GENDER, POLITICAL PARTICIPATION AND LOCAL GOVERNANCE IN THE BUILSA NORTH DISTRICT OF GHANA, GHANA - Adatuu, R.; Apusigah, A. A. (UDS International Journal of Development, 2018)
As a basic level of formal decision-making, the local government system of Ghana, referred to as the Assembly within the context of decentralization, has become the basis for development planning and, resource mobilization. While setting and driving the national agenda remains an issue, the Assemblies are key to the implementation and initiation of development interventions at their level. Since starting in 1988, significant progress has been made in empowering actors to take up and play key roles towards the development of their jurisdictions. As social systems, the Assemblies have not been insulated from the gender inequalities confronting the Ghanaian state. This paper sought to understand the ways and extent of gendering in local governance. It is based on an empirical study conducted in the Builsa North District of Ghana. A cross-sectional survey involving the use of questionnaire, key informant interviews, focus group discussions and desk review served as the tools for data collection. Data analysis was both qualitative and quantitative. The study revealed that women were under-represented at both the general assembly (one out of 45) and unit committee (seven out of 119) levels. There were no women in the Area and Town Councils. This situation was attributed to women’s inability to contest and win elections and the role of traditional and cultural factors resulting in the conclusion that under such constrictions, women compared to men, were limited in their political participation and that when such obstacles are removed women’s fortunes could improve. Keywords: Political Participation, Democracy, Local Governance, Gender Equality, Decentralization